Gamma nail in the management of intertrochanteric fractures of femur in adults - Shah, Faisal Younis; Gul, Irfan Andleeb; Kotwal, Hilal Ahmad (International Surgery Journal, 2018)
Background: Intertrochanteric fracture is an extracapsular fracture of the proximal femur. Gamma nail is a cephalomedullary nail that is emerging as the treatment of choice for intertrochanteric fractures. For intertrochanteric fractures, the use of cephalomedullary devices has increased dramatically to 67% among surgeons over the years. Aims of this study was to observe the results of operative treatment of intertrochanteric fractures with Gamma 3 trochanteric nail. Methods: This prospective study was conducted in the Post Graduate Department of Orthopaedics of Government Medical College, Srinagar. This study included 30 cases of intertrochanteric fractures who attended hospital for bone and joint surgery. Results: Excellent results were obtained in 80% patients and good results were obtained in rest 20% with an average Harris hip score of 93.8. Average time to union was 11.6 weeks. There were no non-unions, screw cut outs or peri-implant fractures. The most common complication was varus malunion occurring in 20% patients. However, significant malunion (greater than 10 degrees) was present in only one patient among them. Conclusions: This study finds Gamma 3 nail to be a versatile, easy to use and dependable implant in intertrochanteric fractures. Gamma 3 nail is an ideal implant for stable as well as unstable intertrochanteric fractures and is a distinct advance over the previous methods of treatment, though it has an initial learning curve.